Socioeconomic Challenges of Adolescent Obesity - Jorge Navarrete-Dualde (Health Economics and Management Review)
Obesity is the epidemic of the century, due to its prevalence, impact on national budgets, loss in a gross domestic product, productivity loss, and impact on mortality, morbidity and quality of life. National behaviour change campaigns have not yet shown acceptable long-term results, and there is a need for higher taxation on unhealthy food. Besides, adolescents are vulnerable and easily targeted by “ultra-funded” sophisticated marketing campaigns. Modest evidence on first and second-line treatments makes bariatric surgery the main treatment of choice. Bariatric surgery could be the standard of care provided to those adolescents who failed weight loss attempts for more than six months and present pre-specified high body mass index and obesity-related comorbidities. To confirm whether the findings extracted from the initial narrative search were still valid, an additional, more profound narrative search, including systematic literature review features, was performed, extracting information before the COVID-19 pandemic from three databases: PubMed from 2018 to 2019; Google Scholar from 2018 to 2019; and The Centre for Reviews and Dissemination from the University of York (from 2010 to 2019). Policymakers need to commit with community health campaigns to change societal behaviour on the real impact of obesity. There is a need for earmarked taxation on unhealthy food to prevent obesity publicly and provide enough funds to increase the provision and reimbursement of bariatric surgery. Bariatric surgery at early ages can reduce the progression of morbid obesity-related comorbidities. However, evaluations of morbidly obese adolescents are not performed in time, due to barriers, which avoid upcoming bariatric surgery procedures. Stakeholders should develop strategies to reduce attrition rate and improve patient retention through juvenile-oriented care. There are still ethical aspects pending since we do not fully know the long-term effects and complications. Given the low impact of public preventive campaigns targeting voluntary behavioural change in the long run, and the lax taxation and regulation on the food industry, decision makers should change their mind on bariatric surgery, from an indulgent waste of money to an effective fund-saver.